Protective Effect of Seleno-L on Cyclophosphamide-Induced Urinary Bladder Toxicity in Rats - Ayhancı, Adnan; Yaman, Suzan; Şahintürk, Varol; Uyar, Ruhi; Bayramoğlu, Gökhan; Şentürk, Hakan; Altuner, Yılmaz; Appak, Sıla; Güneş, Sibel (Humana Press, 2010)
Cyclophosphamide (CP) is a widely used antineoplastic drug, which could cause toxicity of the normal cells due to its toxic metabolites. Its urotoxicity may cause dose-limiting side effects like hemorrhagic cystitis. Overproduction of reactive oxygen species (ROS) during inflammation is one of the reasons of the urothelial injury. Selenoproteins play crucial roles in regulating ROS and redox status in nearly all tissues; therefore, in this study, the urotoxicity of CP and the possible protective effects of seleno-l-methionine (SLM) on urinary bladder of rats were investigated. Intraperitoneal (i.p.) administration of 50, 100, or 150 mg/kg CP induced cystitis, in a dose-dependent manner, as manifested by marked congestion, edema and extravasation in rat urinary bladder, a marked desquamative damage to the urothelium, severe inflammation in the lamina propria, focal erosions, and polymorphonuclear (PMN) leukocytes associated with occasional lymphocyte infiltration determined by macroscopic and histopathological examination. In rat urinary bladder tissue, a significant decrease in the endogenous antioxidant compound glutathione, and elevation of lipid peroxidation were also noted. Pretreatment with SLM (0.5 or 1 mg/kg) produced a significant decrease in the bladder edema and caused a marked decrease in vascular congestion and hemorrhage and a profound improvement in the histological structure. Moreover, SLM pretreatment decreased lipid peroxide significantly in urinary bladder tissue, and glutathione content was greatly restored. These results suggest that SLM offers protective effects against CP-induced urinary bladder toxicity and could be used as a protective agent against the drug toxicity. © 2009 Humana Press Inc.
Keywords: Cyclophosphamide; Cytoprotectivity; Rattus; Seleno-l-methionine; Urotoxicity